2010
DOI: 10.1007/978-1-4419-1528-3_13
|View full text |Cite
|
Sign up to set email alerts
|

The Tetrapyrrole Biosynthetic Pathway and Its Regulation in Rhodobacter capsulatus

Abstract: The purple anoxygenic photosynthetic bacterium Rhodobacter capsulatus is capable of growing in aerobic or anaerobic conditions, in the dark or using light, etc. Achieving versatile metabolic adaptations from respiration to photosynthesis requires the use of tetrapyrroles such as heme and bacteriochlorophyll, in order to carry oxygen, to transfer electrons and to harvest light energy. A third tetrapyrrole, cobalamin (vitamin B12), is synthesized and used as a cofactor for many enzymes. Heme, bacteriochlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 95 publications
(159 reference statements)
2
38
0
Order By: Relevance
“…Although this expression of genes for the enzymes of BChl biosynthesis under anoxic conditions is consistent with the laboratory studies for C. aurantiacus (Oelze, 1992) and anoxygenic phototrophic proteobacteria (Ponnampalam et al, 1995;Gregor and Klug, 1999;Zappa et al, 2010), the Chloroflexus spp. and Roseiflexus spp.…”
Section: Bacteriochlorophyll (Bchl) Biosynthesissupporting
confidence: 90%
“…Although this expression of genes for the enzymes of BChl biosynthesis under anoxic conditions is consistent with the laboratory studies for C. aurantiacus (Oelze, 1992) and anoxygenic phototrophic proteobacteria (Ponnampalam et al, 1995;Gregor and Klug, 1999;Zappa et al, 2010), the Chloroflexus spp. and Roseiflexus spp.…”
Section: Bacteriochlorophyll (Bchl) Biosynthesissupporting
confidence: 90%
“…Allosteric control of HemE would provide Halomonas a means by which to control flux through these pathways based on B 12 availability, and suggests a fundamentally new role for B 12 in cellular metabolism. Prior reports on control of the tetrapyrrole biosynthetic pathway in other microbes have identified regulatory feedback controls by B 12 -dependent riboswitches (27) and redox signaling cascades (28). Taking these data together, we find that vitamin B 12 regulation of these steps could result in redirection of metabolism between biosynthesis of heme versus B 12 biosynthesis.…”
Section: Resultssupporting
confidence: 52%
“…Short reviews within otherwise focused manuscripts can be found (35)(36)(37)(38)(39), and there is an excellent review of tetrapyrrole biosynthesis in Rhodobacter capsulatus (40). The last broad-scope genome-based review of prokaryotic heme synthesis was reported over a dozen years ago by O'Brian and Thony-Meyer (41).…”
Section: Introduction Wmentioning
confidence: 99%